PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM KERJA TERHADAP PRODUKTIVITAS GURU SMP NEGERI DI KECAMATAN PALMERAH JAKARTA BARAT - Mohamad Najib Anis Subekhi (Jurnal Manajemen Pendidikan, 2017)
This study aims to determine the effect of transformational leadership and work climate on teacher productivity State Junior High School in Palmerah Sub-district, West Jakarta.The method used ini this research is survey method with path analysis techniques. This study used a population of teachers State Junior High School in Palmerah Sub-district, West Jakarta much as 200 teachers. Sampling techniques in this study is proportional random sampling methode.Based on the results of the study can be summarized as follows: Firstly, there is the effect of transformational leadership on teacher productivity; Secondly, there is the effect of work climate on teacher productivity; Third, there is the effect of transformational leadership on work climate.